How Positioning Affects English Learners' Social Interactions Around Reading. Issue 3 (3rd July 2019) - Protacio, Maria Selena
Abstract : Social interactions are an essential element of students' reading engagement. Social interactions around reading are an essential component to English learners' (ELs) reading engagement specifically as they provide opportunities to share cultural, linguistic, and intellectual resources. This article examines the effect of positioning on ELs' social interactions around reading. With a storyline of middle school ELs, the article discusses how self-positioning and other-positioning influence the quality and types of social interactions around reading in which ELs participate. The article concludes with instructional implications for how educators can ensure that ELs have access to positive social reading interactions as a way to facilitate students' reading engagement.